Hardware Prototyping Of An Efficient Image Compression System In Real-Time For Mobile Communication - Akter, Masuma (2008)
This project uses a wavelet-based image compression algorithm using Set Partitioning in Hierarchical Trees (SPIHT), as it is found to be the most suitable for real-time imaging application.